Rancang Bangun Robot Sepak Bola Beroda Menggunakan Kamera Huskylens - Afridho, Jimmy; Riyanto, Agus; Satriyo, Satriyo; Ridhwan Sufandi, Muhammad; Indah Rahayu, Wiwit (Electrical Network Systems and Sources, 2024)
A wheeled soccer robot is designed to move and kick the ball to score goals. This robot is equipped with wheels and motors for movement, a camera as its "eyes," and a servo motor for kicking the ball. One of the cameras that can be used is the HuskyLens, an artificial intelligence camera specifically developed for robotics applications. The use of HuskyLens in the soccer robot has the potential to change how the robot interacts with the ball, opponents, and its environment in a smarter and more adaptive way. The robot is designed to move and kick the ball automatically. Components used include an Arduino Uno microcontroller, HuskyLens camera, L293D motor driver shield, MG90S servo motor, proximity sensor, DC gearbox motor, and mecanum wheels. This research involved direct observation of several tests to evaluate the effectiveness of the components, particularly the HuskyLens camera, as the robot's "eyes." The results of the research and tests show that the robot successfully detects and approaches the ball to kick it. The camera can detect the ball at a distance of up to 12 meters, and the robot can kick the ball from a distance of up to 1.4 meters. Keywords : Robotics, huskylens, l293d motor driver shield, proximity sensor, Arduino Uno microcontroller.